# 3-3×6+2=13

When it comes to the equation 3-3×6+2=13, it’s important to understand the order of operations, also known as PEMDAS (Parentheses, Exponents, Multiplication and Division, and Addition and Subtraction). By following these rules, we can easily solve the equation. Here’s a clear and concise breakdown:

1. Start by simplifying any parentheses or brackets in the equation. In this case, there are none, so we move to the next step.
2. Next, evaluate any exponents or powers. Again, there are none in this equation, so we move forward.
3. Now, we perform multiplication and division from left to right. In the equation, we have 3 multiplied by 6, which equals 18.
4. Substituting the result of the multiplication, we rewrite the equation as 3 – 18 + 2 = 13.
5. Finally, we perform addition and subtraction from left to right. Subtracting 18 from 3 gives us -15, and then adding 2 to -15 gives us the final answer, which is 13.

To summarize: 3 – 3 x 6 + 2 = 13 3 – 18 + 2 = 13 -15 + 2 = 13 -13 = 13 13 = 13